Hipocrisy of Latinamerican Philosophy - Silveira, Ronie Alexsandro Teles (Disertaciones, 2023)
Criticism is a kind of touchstone for all Latin American philosophy. This is because we have been critical to the extent that we learn the epistemological procedures of Western philosophy. However, the criticism does not have hegemony in Latin America because it acquired divergent functionalities in relation to the original model. That's why we're critical and we're not. The accountability with this ambiguity shows us that we have been unintentionally hypocritical. . The evidence of this is that we have not been able to give up criticism to assess the effective situation of this ambiguity. With this, we not only incur a logical circle form, but we slip into the comfort of European philosophy. To abandon this involuntary hypocrisy, we only have the way of discovering that we are not Europeans.
Keywords: Critic; Latin American Philosophy; Western Philosophy; Hipocrisy